Exploring the spatiotemporal changes and influencing factors of urban resilience based on Scale-Density-Morphology—A case study of the Chengdu-Deyang-Mianyang Economic Belt, China - He, Wei; Zheng, ShiWei; Zhao, XiaoQuan (Frontiers in Environmental Science, 2023)
An in-depth study of urban resilience is of great practical significance for promoting urban security and sustainable development and promoting the harmonious development of the urban population, economy, and ecology. This paper constructs urban resilience evaluation indicators based on Scale-Density-Morphological, adopts the "polyhedron method" to evaluate the urban resilience of the Chengdu-Deyang-Mianyang Economic Belt from 2010 to 2020, analyzes the temporal and spatial changes in urban resilience, and explores the impact of natural. social. economic and other factors on urban resilience, to provide a basis for regional sustainable development. The results show that (1) the overall level of urban resilience is not high, and it shows an obvious downward trend and imbalance. The comprehensive urban resilience dropped from 0.296 in 2010 to 0.213 in 2020. The proportion of districts and counties with high urban resilience is relatively small and continuously decreasing. Differences in urban resilience within regions are significant and gradually increasing, and there is an obvious imbalance in the development of urban security. (2) Urban resilience presents the spatial distribution characteristics of low resilience, continuous expansion of low resilience cities, and shrinking distribution of high resilience and high resilience cities. The spatial evolution is mainly characterized by a rapid decline and fluctuating decline. (3) The different effect factors affecting the spatial differentiation of urban resilience vary from time to time. The ecological factor represented by the per capita ecological land area has gradually become the primary factor. The influence of the interaction of the factors is greater than the influence of the individual factors, including the nonlinear enhancement and dual factor-enhanced two types.